Poetic Sloganeering Walker Dance Park Music's Essence reviewed - Felsenburg, Ben (Dance Books Ltd., Alton,Hampshire (UK), 2005)
Review of Walker Dance Park Music's Essence. PALABRAS CLAVE: Essence, Walker Dance Park Music, dance-opera.